THE EFFECT OF CANDY CONSUMPTION THAT CONTAIN SORBITOL MATERIALS ON THE DENTAL PLAQUE INDEX IN 2018 DENTAL NURSING STUDENTS - Idham Halid; Junaidi Junaidi (Poltekkes Kemenkes Jambi, 2018)
ABSTRACT Sorbitol is a snack of a type of sugar alcohol made from tapioca flour, and is a sweet candy substitute for sugar. Candy snacks such as sorbitol are rarely found in stalls / shops, many of which are marketed in mini markets or supermarkets. Sorbitol candy can be made as an alternative to reduce the amount of sugar we consume because of the sweet taste but not damage the teeth. The purpose of this study was to determine the effect of consuming candy containing sorbitol on dental plaque scores. The type of research used was the experiment with the design of the pre-test and post-test with control group. The number of samples was 30 Students of the Dental Nursing Department in Jambi. The sample was divided into two groups, the treatment group and the control group did not consume candy containing sorbitol. Data analysis using t test. Plaque was measured using a modified plaque index Quigley & Hein (1970) before and after consuming sweets containing sorbitol. the independent variable is candy containing sorbitol and as a dependent variable is the plaque index. Research Results Shows that there are significant differences before and after consuming sweets with Sorbitol ingredients with a sig value of 0.000 (<0.005). For the average value before the consumption of sweets with Sorbitol ingredient is 4,807 and after consuming sweets with sorbitol ingredients with an average of 2,273. Candies containing sorbitol can be recommended as an alternative candy to prevent caries in children and adults.